Model-based predictive control for bicycling in urban intersections. (September 2016) - Portilla, C.; Valencia, F.; Espinosa, J.; Núñez, A.; De Schutter, B.
Highlights: Model predictive control is proposed for improving the efficiency of bicycling. The dynamics of bicycling were incorporated in the control of traffic lights. Improvements when measuring or estimating the vehicle and bicycle demand. Abstract: In this paper, a model predictive control approach for improving the efficiency of bicycling as part of intermodal transportation systems is proposed. Considering a dedicated bicycle lanes infrastructure, the focus in this paper is to optimize the dynamic interaction between bicycles and vehicles at the multimodal urban traffic intersections. In the proposed approach, a dynamic model for the flows, queues, and number of both vehicles and bicycles is explicitly incorporated in the controller. For obtaining a good trade-off between the total time spent by the cyclists and by the drivers, a Pareto analysis is proposed to adjust the objective function of the MPC controller. Simulation results for a two-intersections urban traffic network are presented and the controller is analyzed considering different methods of including in the MPC controller the inflow demands of both vehicles and bicycles.